A fiber bundle-plastic chain model for quasi-brittle materials under uniaxial loading. (13th November 2015) - Shan, Zhi; Yu, Zhiwu
Abstract: A fiber bundle-plastic chain model for quasi-brittle materials under both uniaxial compression and tension conditions is developed. By introducing a plastic chain model into the fiber bundle model, a bundle-chain model for quasi-brittle materials is proposed with physical considerations. The model achieves a novel and convenient approach to describe the stochastic effective stress-driven plasticity. It is found that the numerical solutions obtained with this model agree with experimental results when subjected to both monotonic and cyclic uniaxial loading. The model generates a numerical solution with higher accuracy than the present models, when compared with the experimental results on certain problems. An example is shown which utilizes this model to describe the stochastic properties of a constitutive model given as standard. Furthermore, the difference between the existing plastic fiber bundle models in the literature and this model is also obtained in this work.